Fewer Degrees of Separation Means More Precision in Software Projects. - Chorn, Jim (Communications of the ACM, 2006)
A letter to the editor is presented concerning an article by Phillip G. Armour, titled "Software: Hard Data," which appeared in the September 2006 issue.